Thoughts on the Establishment of the Multilateral Investment Guarantee Agency - Dietrich Kebschull (Intereconomics, 1986)
After years of preparatory work, the World Bank's Board of Governors has now given its assent to the Convention Establishing the Multilateral Investment Guarantee Agency (MIGA) for foreign investment in developing countries. Is such a system adequate to mobilise large amounts of additional capital?
Keywords: 330